2016
DOI: 10.1016/j.nima.2016.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of the dielectric wakefield accelerators in the SINBAD facility at DESY

Abstract: Short, high-brightness relativistic electron bunches can drive ultra-high wakefields in the dielectric 7 wakefield accelerators (DWFAs). This effect can be used to generate high power THz coherent Cherenkov

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The thin dielectric layer of δ = 25 µm was chosen to achieve the experimental aim of short pulse, tunable THz output. Additionally other simulation studies have shown that thin dielectric layers can be used when coupling to short electron pulses, for example those from laser wakefield accelerated bunches [22,23].…”
Section: Dlw Designmentioning
confidence: 99%
“…The thin dielectric layer of δ = 25 µm was chosen to achieve the experimental aim of short pulse, tunable THz output. Additionally other simulation studies have shown that thin dielectric layers can be used when coupling to short electron pulses, for example those from laser wakefield accelerated bunches [22,23].…”
Section: Dlw Designmentioning
confidence: 99%
“…As previously studied in [21], the DLW structure has the potential to serve as a dechirper to compensate the positive energy chirp of a LWFA-accelerated bunch, in which the electrons in the bunch head have lower energy than those in the tail. In this paper, we report detailed numerical simulations of an energy dechirper that is based on a rectangular (slab-symmetric) DLW structure, with the help of the CST Wakefield Solver and PIC Solver [26].…”
Section: Introductionmentioning
confidence: 99%
“…The DLWs have been widely studied both theoretically and experimentally making use of the AWA facility at ANL [11,12], the ATF facility at BNL [13,14], and the FACET facility at SLAC [15,16]. There are many other dedicated facilities being constructed or planned to study advanced electron accelerator concepts including the DLWs, for example, CLEAR at CERN [17,18], CLARA in Daresbury Laboratory [19], SINBAD at DESY [20,21], SPARC_LAB at INFN [17,22], etc. These facilities can generally provide electron beams with a broad range of bunch parameters and time structures depending on operating mode.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric wakefield acceleration (DWA) in planar and circular dielectric structures has seen major developments in understanding the maximum achievable accelerating gradients [1], dielectric breakdown limits [2] as well as applications for beam compression [3], modulation [4] and correlated energy spread compensation [5]. Extremely compact DWA-based accelerators have the potential to drive the next generation of free electron lasers and linear colliders [6,7].…”
Section: Introductionmentioning
confidence: 99%